2009
DOI: 10.1002/ijc.24816
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule XIAP inhibitors sensitize childhood acute leukemia cells for CD95‐induced apoptosis

Abstract: Escape of apoptosis may contribute to treatment failure in childhood acute lymphoblastic leukemia (ALL) calling for new approaches to overcome apoptosis resistance. Here, we provide for the first time evidence that small molecule inhibitors that target the anti-apoptotic protein X-linked inhibitor of apoptosis (XIAP) sensitize ALL cells for CD95-induced apoptosis. XIAP inhibitors at subtoxic concentrations, but not a structurally related control compound, act synergistically with agonistic anti-CD95 antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…As the IAP inhibitors antagonize XIAP besides cIAP1 and cIAP2, 18 the neutralization of the XIAPimposed inhibition of effector caspases by IAP inhibitors might contribute to promote IAP inhibitor-and AraC-induced apoptosis, as we recently reported for death receptor-induced apoptosis. 17,28 Also, our findings indicate that DNA damage might promote RIP1/FADD/caspase-8 formation independently of autocrine/paracrine TNFa signaling.…”
Section: Discussionmentioning
confidence: 57%
“…As the IAP inhibitors antagonize XIAP besides cIAP1 and cIAP2, 18 the neutralization of the XIAPimposed inhibition of effector caspases by IAP inhibitors might contribute to promote IAP inhibitor-and AraC-induced apoptosis, as we recently reported for death receptor-induced apoptosis. 17,28 Also, our findings indicate that DNA damage might promote RIP1/FADD/caspase-8 formation independently of autocrine/paracrine TNFa signaling.…”
Section: Discussionmentioning
confidence: 57%
“…Previously, we reported that small-molecule inhibitors of IAP proteins such as Smac mimetics act in concert with other cytotoxic stimuli, for example death receptor ligands such as TRAIL and CD95 ligand, chemotherapeutic drugs, or irradiation, in ALL or other cancer entities. 24,25,38,[40][41][42][43] Second, we identify a novel underlying molecular mechanism of this synergistic interaction by showing that BV6 and dexamethasone act in concert to trigger proteasomal degradation of IAP proteins, which in turn promotes the assembly of the ripoptosome, a cytosolic cell death complex ( Figure 6). Several lines of evidence support this conclusion, as follows:…”
Section: Discussionmentioning
confidence: 99%
“…22 We previously reported that small-molecule IAP inhibitors enhance death receptoror chemotherapy-induced apoptosis in childhood leukemia. [23][24][25] However, the question of whether or not targeting IAP proteins represents a suitable strategy to bypass GC resistance in ALL has not yet been answered. Therefore, in the present study we investigated the question of whether or not neutralization of XIAP, cIAP1, and cIAP2 by the small-molecule Smac mimetic BV6 19 can enhance the antileukemic activity of GC against childhood ALL.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in ALL subtoxic concentrations of IAP inhibitors were described to synergistically induce apoptosis and to reduce clonogenic survival in combination with agonistic anti-CD95 antibodies or MegaFas ligand, a hexameric form of CD95 ligand, whereas they failed to sensitize normal peripheral blood lymphocytes for CD95-mediated apoptosis (47). The clinical relevance of this combination strategy was underscored by experiments performed in primary leukemic blasts freshly isolated from children with ALL, which similarly showed a synergistic induction of apoptosis of IAP inhibitors and MegaFas ligand (47). Also, the Smac mimetic BV6 was shown to sensitize Jurkat T-ALL cells that express key components of the death receptor pathway such as FADD or caspase-8 to CD95-mediated apoptosis, whereas FADD-or caspase-8-deficient cells remained resistant to this combination (48).…”
Section: Smac Mimetics In Combination With Cd95mentioning
confidence: 99%